2018
DOI: 10.1111/eth.12799
|View full text |Cite
|
Sign up to set email alerts
|

Female clustering in cockroach aggregations—A case of social niche construction?

Abstract: Individuals in groups can suffer costs through interactions with adversarial or unknown conspecifics. Social niche construction allows individuals to buffer such potential costs by only engaging in preferred associations. This may be particularly beneficial in insect aggregations, which are often large and highly fluid. However, little is known regarding the structuring of such aggregations. Here we use social network analyses to test for fine‐scale social structure in resting aggregations of the sub‐social co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 81 publications
(118 reference statements)
0
13
0
Order By: Relevance
“…Some have suggested that females prefer to interact with other females to buffer against destabilizing interactions with males. Studies in baboons, horses, and others have shown that the presence of strong stable female relationships are associated with increased survival and fitness (Cameron, Setsaas & Linklater, 2009;Carter, Lee, Marshall, Ticó & Cowlishaw, 2015;Silk, et al 2009Silk, et al , 2010 and studies in the cockroach Diploptera punctata and guppies have suggested that female aggregations limit intrusions by males (Stanley, Liddiard Williams & Preziosi, 2018). If male interactions have a destabilizing effect, we should also observe that they are preferentially avoided.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Some have suggested that females prefer to interact with other females to buffer against destabilizing interactions with males. Studies in baboons, horses, and others have shown that the presence of strong stable female relationships are associated with increased survival and fitness (Cameron, Setsaas & Linklater, 2009;Carter, Lee, Marshall, Ticó & Cowlishaw, 2015;Silk, et al 2009Silk, et al , 2010 and studies in the cockroach Diploptera punctata and guppies have suggested that female aggregations limit intrusions by males (Stanley, Liddiard Williams & Preziosi, 2018). If male interactions have a destabilizing effect, we should also observe that they are preferentially avoided.…”
Section: Discussionmentioning
confidence: 88%
“…Across taxa there has been a tendency for females to form strong connections with other females, whereas males disperse to neighboring groups (Ward & Webster, 2016). In mammals (Stanley, Liddiard Williams, & Preziosi, 2018), birds (Kohn, King, Scherschel, & West, 2011), and insects (Stanley, Williams, Preziosi 2017) females have been observed to form cohesive female subgroups within the larger group. Strong connections among familiar females often have beneficial consequences for females such as reduced risk from male harassment (Cameron, Setsaas & Linklater,.…”
Section: Introductionmentioning
confidence: 99%
“…Female-female social clustering may therefore reflect an effective strategy to avoid harassment. Similar patterns in cockroaches, D. punctata, have led to the suggestion that females may engineer the sex ratio of their social environment, biasing it towards females to avoid costly male harassment [26]. Similarly, female eastern mosquitofish school closer together in the presence of males, which dilutes male harassment [32,63].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the effect of female competition might be counteracted by the need for females to group together (e.g. to avoid male harassment [26,31,35]). Intersexual associations were closely related to patterns of sexual behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation